PENGARUH IKLIM ORGANISASI, STRES KERJA DAN KOMITMEN KARYAWAN TERHADAP KEINGINAN KELUAR KARYAWAN HOTEL MERCURE KUTA - Setyowati, Astri; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 6 No 5 (2017), 2017)
Intention to quit is negative perception of employees with their work which has the potential to leave the organization when they feel discomfort and fatigue in work. So that employees do not have a high level of intention to quit, an organization need to pay attention to the factors that affect the desire to get out. The purpose of this research is to know the influence of organizational climate, work stress and employee commitment on intention to quit of the employees. This research was conducted at the Hotel Mercure Kuta-Bali. The samples used were 92 employees with probability sampling method. Methods of data collection is questionnaires and interviews. The data analysis technique used multiple regression analysis. The analysis showed that the variables of organization climate has negative influence on intention to quit, work stress has positive influence on intention to quit, and employee commitment has negative influence on intention to quit.
Keywords: organizational climate, work stress, employee commitment, intention to quit